Extracellular miR-574-5p Induces Osteoclast Differentiation via TLR 7/8 in Rheumatoid Arthritis - Hegewald, Anett B.; Breitwieser, Kai; Ottinger, Sarah M.; Mobarrez, Fariborz; Korotkova, Marina; Rethi, Bence; Jakobsson, Per-Johan; Catrina, Anca I.; Wähämaa, Heidi; Saul, Meike J. (Frontiers in Immunology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by synovial inflammation and joint destruction. Cell-derived small extracellular vesicles (sEV) mediate cell-to-cell communication in the synovial microenvironment by carrying microRNAs (miRs), a class of small non-coding RNAs. Herein, we report that sEV from synovial fluid promote osteoclast differentiation which is attributed to high levels of extracellular miR-574-5p. Moreover, we demonstrate for the first time that enhanced osteoclast maturation is mediated by Toll-like receptor (TLR) 7/8 activation mediated by miR-574-5p binding. This is a novel mechanism by which sEV and miRs contribute to RA pathogenesis and indicate that pharmacological inhibition of extracellular miR-574-5p might offer new therapeutic strategies to protect osteoclast-mediated bone destruction in RA.